Improved Cardiovascular Risk among Hispanic Border Participants of the Mi Corazón Mi Comunidad Promotores De Salud Model: The HEART II Cohort Intervention Study 2009–2013 - de Heer, Hendrik Dirk; Balcazar, Hector G.; Wise, Sherrie; Redelfs, Alisha H.; Rosenthal, E. Lee; Duarte, Maria O. (Frontiers in Public Health, 2015)
Abstract Background Community resources (parks, recreational facilities) provide opportunities for health promotion, but little is known about how to promote utilization of these resources and their impact on cardiovascular disease risk (CVD). Methods This cohort study evaluated the impact of an intervention called Mi Corazon Mi Comunidad (MiCMiC), which consisted of promoting use of community physical activity and nutrition resources by Promotoras de Salud/Community Health Workers. Participants were assessed at baseline and following the 4-month intervention. Attendance records were objectively collected to assess utilization of intervention programming. Results A total of 5 consecutive cohorts were recruited between 2009 and 2013. Participants were mostly females (86.0%), on average 46.6 years old, and 81% were low in acculturation. Participants who completed follow-up (n=413) showed significant improvements in reported health behaviors and body composition. Higher attendance significantly predicted greater improvements. The baseline to 4-month change for the highest versus the lowest attendance quartiles were (-5.2 lbs vs. +0.01 lbs, p<.001), waist circumference (-1.20 inches vs. -0.56 inches, p=.047), hip circumference (-1.13 inches vs. -0.41 inches, p<.001); hours of exercise/week (+3.87 hours vs. +0.81 hrs, p<.001), proportion of participants eating 5 servings of fruits and vegetables/day (+54.7% vs. 14.7%, p<.001). Conclusions Following the Promotora-led MiCMiC intervention, substantial improvements in health behaviors and modest improvements in cardiovascular risk factors were found. Greater utilization of community resources was associated with more favorable changes. This study provided preliminary evidence for the effectiveness of Promotora-led interventions for promoting use of existing community resources in CVD risk reduction. Key Words: Community resources, community health workers, U.S.- Mexico border, Hispanic, cardiovascular disease, cohort